PENERAPAN PERATURAN WALIKOTA PADANG NOMOR 25 TAHUN 2016 TENTANG KAWASAN TANPA ROKOK DI SMP NEGERI 13 KOTA PADANG - Jayanti Jayanti; Nora Eka Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This article aims to describe the Application of Padang Mayor Regulation Number 25 Year 2016 on Non-Smoking Areas in SMP Negeri 13 Padang City. Based on the regulation of the mayor of padang which includes non-smoking areas are Health Service Places, Teaching and Learning Process, Children Play, Worship, Public Transportation, Workplaces And other Public Places that have been determined. SMPN 13 is a place for teaching and learning. This research uses George C Edwar III Theory related to Communication, Resources, Disposition and Bureaucracy. This research uses descriptive qualitative method with Porposive Sampling informant selection technique. Data collection techniques are carried out with interviews, observations and documentation. The result obtained from research at SMPN 13 Padang city is the implementation of Padang Mayor Regulation No. 25 of 2016 on non-smoking areas